2006
DOI: 10.1111/j.1529-8817.2006.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

POLYPHASIC STUDY OF ANTARCTIC CYANOBACTERIAL STRAINS1

Abstract: We isolated 59 strains of cyanobacteria from the benthic microbial mats of 23 Antarctic lakes, from five locations in two regions, in order to characterize their morphological and genotypic diversity. On the basis of their morphology, the cyanobacteria were assigned to 12 species that included four Antarctic endemic taxa. Sequences of the ribosomal RNA gene were determined for 56 strains. In general, the strains closely related at the 16S rRNA gene level belonged to the same morphospecies. Nevertheless, diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
174
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(199 citation statements)
references
References 39 publications
(68 reference statements)
16
174
0
8
Order By: Relevance
“…Many bacteria and microbial eukaryotes have been identified as possibly endemic to Antarctica, including several cyanobacterial species (Komárek, 1999;Taton et al, 2006b). However, our clone-library analyses indicate that three taxa previously identified as Antarctic endemics (Phormidum priestleyi Fritsch, L. frigida (Fritsch) Anagn.…”
Section: Biogeography Of Polar Cyanobacteriamentioning
confidence: 76%
See 1 more Smart Citation
“…Many bacteria and microbial eukaryotes have been identified as possibly endemic to Antarctica, including several cyanobacterial species (Komárek, 1999;Taton et al, 2006b). However, our clone-library analyses indicate that three taxa previously identified as Antarctic endemics (Phormidum priestleyi Fritsch, L. frigida (Fritsch) Anagn.…”
Section: Biogeography Of Polar Cyanobacteriamentioning
confidence: 76%
“…and Kom. ; Komárek, 1999;Taton et al, 2006b) were more than 99% similar to sequences from the Canadian High Arctic (Table 2); for example, ArC05 is 99.6% similar to P. priestleyi (ANT.PROGRESS2.6; AY493585) and ArC13 is 99.8% similar to L. antarctica (ANT.LH18.1; AY493607). Furthermore, several of the uncultured cyanobacterial clones from East Antarctica and the McMurdo Dry Valleys identified as endemic, had the highest percentage match, up to 99.9%, to some of our High Arctic sequences.…”
Section: Biogeography Of Polar Cyanobacteriamentioning
confidence: 84%
“…Poorly explored areas or unusual environments have become critical for the discovery of novel compounds and bacteria (Saadoun and Gharaibeh, 2003;Lam, 2007;Newman and Cragg, 2007;Thakur et al, 2007). Therefore, soil samples taken from the Antarctic, one of the coldest and most poorly explored regions of the world, present good potential for the discovery of novel bioactive metabolites and compounds from microorganisms like bacteria (Marinelli et al, 2004;Tindall, 2004;Taton et al, 2006). This study was conducted to investigate the diversity and antimicrobial bioactivity of proteobacteria by performing isolation, molecular identification, molecular characterization, and bioactive secondary metabolite screening using 4 high-throughput screening models.…”
Section: Discussionmentioning
confidence: 99%
“…Poorly explored areas like the Antarctic present significant potential for the discovery of novel microorganisms like bacteria and biological active metabolites (Moncheva et al, 2002;Marinelli et al, 2004;Tindall, 2004;Taton et al, 2006;Bull and Stach, 2007). Barrientos Island is located at 62°24'S, 59°47'W, at the north entrance to the English Strait between Greenwich and Robert Islands.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these Cyanobacterial sequences were closely related to Leptolyngbya isolates from Antarctica (Taton et al 2006), and a separate study has shown that Leptolyngbya species dominate the microbial communities on stromatolite benthic samples from the alkaline (pH 10.4) lake Untersee in Antarctica (Andersen et al 2011). In addition, Cyanobacterial stromatolite-related sequences were also detected in the microbial mat sample (40% of the clones) from the Del Puerto Ophiolite, and have been linked to biological precipitation of carbonates (Blank et al 2009).…”
mentioning
confidence: 90%